Preparation and properties of epoxy-cross-linked porous polybenzimidazole for high temperature proton exchange membrane fuel cells - Wang, Shuang; Zhao, Chengji; Ma, Wenjia; Zhang, Gang; Liu, Zhongguo; Ni, Jing; Li, Mingyu; Zhang, Na; Na, Hui (Journal of membrane science, 2012)
[Display omitted] ► The cross-linking reaction could be completed by heating at a low temperature. ► The porous PBI membranes could effectively elevate doping level. ► The CpPBI-10 could be suitable for HT-PEMFCs applications. A new approach has been proposed to obtain high-temperature proton exchange membranes based on novel cross-linked porous polybenzimidazole (PBI). The cross-linked porous PBI membranes (CpPBI) were prepared by leaching out a low-molecular-weight compound dibutyl phthalate and mixing 4,4′-diglycidyl (3,3′,5,5′-tetramethylbiphenyl) epoxy resin as a cross-linker. The porous PBI membranes (pPBI) were also prepared for comparison. Compared with pPBI membranes, the mechanical properties and the chemical stability of CpPBI membranes were significantly improved. Both the uncross-linked and cross-linked membranes were doped with phosphoric acid, which may be used as proton exchange membranes for high temperature fuel cell. The doping level of all the pPBI membranes was higher than that of pristine PBI, thus leading to a higher proton conductivity. Especially the CpPBI-10 (with a cross-linker content of 10wt.% and a porogen content of 50wt.%) had a relative high proton conductivity of 0.046Scm−1 at 200°C, which is higher than some of the known porous PBI membranes measured under similar conditions. All the remarkable results of the epoxy-cross-linked porous PBI membranes indicated that the CpPBI membranes could be a suitable candidate for high temperature proton exchange membrane fuel cell (HT-PEMFC) applications.